„Wszyscy jesteśmy Azjaci!”, czyli Starego Poety pytania o tożsamość. Perspektywa postkolonialna - Kałowska, Agnieszka (Czytanie Literatury. Łódzkie Studia Literaturoznawcze, 2012)
The article aims to analyze Jarosław Iwaszkiewicz’s poem entitled “The Asians”, the first work from his volume “The Weather Map”. The starting point for reflection is the motto of the poem - a conversation of three people in a theater foyer. The subject of this short exchange is the border between Europe and Asia, not the geographical but the cultural one. The dialogue can also be interpreted as an attempt to answer the question of the strength of the impact of the Euro-Asian empire — Russia. The author of the article endeavors to read the poem as the poet’s attempt to interpret his own biography. An important context is a poem by Alexander Blok, “The Scythians” written in 1918.